A modified 'skeleton/skin' strategy for designing CoNiP nanosheets arrayed on graphene foam for on/off switching of NaBH4 hydrolysis. Issue 45 (17th July 2020) - Li, Jinghua; Hong, Xianyong; Wang, Yilong; Luo, Yumei; Li, Bin; Huang, Pengru; Zou, Yongjin; Chu, Hailiang; Zheng, Shiyou; Sun, Lixian; Xu, Fen; Du, Yong; et al.
Abstract : Schematic diagram of the preparation, cycles and the kinetics of the Ni/GF/CoNiP nanosheet catalyst. Abstract : CoNiP nanosheet array catalysts were successfully prepared on three-dimensional (3D) graphene foam using hydrothermal synthesis. These catalysts were prepared using 3D Ni–graphene foam (Ni/GF), comprising nickel foam as the 'skeleton' and reduced graphene oxide as the 'skin'. This unique continuous modified 'skeleton/skin' structure ensure that the catalysts had a large surface area, excellent conductivity, and sufficient surface functional groups, which promoted in situ CoNiP growth, while also optimizing the hydrolysis of sodium borohydride. The nanosheet arrays were fully characterized and showed excellent catalytic performance, as supported by density functional theory calculations. The hydrogen generation rate and activation energy are 6681.34 mL min −1 g −1 and 31.2 kJ mol −1, respectively, outperforming most reported cobalt-based catalysts and other precious metal catalysts. Furthermore, the stability of mockstrawberry-like CoNiP catalyst was investigated, with 74.9% of the initial hydrogen generation rate remaining after 15 cycles. The catalytic properties, durability, and stability of the catalyst were better than those of other catalysts reported previously.